2013
DOI: 10.1075/fol.20.2.05mag
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical metaphor in Swedish monolingual and multilingual upper secondary school students’ writing

Abstract: This partly longitudinal study applies the theoretical framework of Systemic Functional Linguistics to second language writing to investigate the use of grammatical metaphor (GM; non-congruent realizations of meaning, e.g. nominalizations) in 365 texts written by Swedish mono-and multilingual students in grades 9 and 11. According to the analysis, older students and monolingual students make greater use of GM than younger students and multilingual students. Multilingual students with early and late ages of ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Therefore, it is possible to establish a correlation between their choices and the factors behind them, so that learners and instructors could ultimately infer statistically which areas facilitate better the needed successful separation between literal and figurative modes, and implement these into their teaching-learning routines. example, Magnusson (2013) reported that older L2 English students and Swedish monolingual students made greater use of grammatical metaphor, which establishes an implicit link between language proficiency and using figurative uses of the language; this tallies with other studies on the effect of age in adolescent metaphoric competence (deckert et al, 2018; willinger et al, 2019). For our study, these findings would imply that greater language proficiency (whether being a L1 or a more competent L2 speaker) aids to the critical separation of literal and figurative modes.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, it is possible to establish a correlation between their choices and the factors behind them, so that learners and instructors could ultimately infer statistically which areas facilitate better the needed successful separation between literal and figurative modes, and implement these into their teaching-learning routines. example, Magnusson (2013) reported that older L2 English students and Swedish monolingual students made greater use of grammatical metaphor, which establishes an implicit link between language proficiency and using figurative uses of the language; this tallies with other studies on the effect of age in adolescent metaphoric competence (deckert et al, 2018; willinger et al, 2019). For our study, these findings would imply that greater language proficiency (whether being a L1 or a more competent L2 speaker) aids to the critical separation of literal and figurative modes.…”
Section: Introductionsupporting
confidence: 80%
“…AnALySIS oF ThE RELATIonShIP bETwEEn STUdEnTS' PRoFICIEnCy LEvEL And ThEIR AbILITy To IdEnTIFy FIgURATIvE LAngUAgE fundamentally disagrees with studies carried out with younger informants; bothMagnusson (2013) and willinger et al's (2019) assertion that metaphor identification and comprehension invariably increase with age seems to be applicable to the transition to adolescence, but not necessarily be the case with adult learners.…”
mentioning
confidence: 95%
“…She also found that all texts in the highest grades contain metaphor clusters, indicative of a qualitative change that is needed to discuss abstract topics (cf. Magnusson, 2013, who found a significant increase in the use of grammatical metaphor between students in secondary and upper secondary school).…”
Section: A Scandinavian Perspectivementioning
confidence: 97%
“…This construct has found extensive use in modern Chinese contexts, particularly in daily conversation, owing to its expressive power and semantic characteristics, which are easily discernible through the lens of grammatical metaphor. Thus, these words and phrases can be analyzed and explained in depth from a number of perspectives [4]. Moreover, it is easy to associate grammar metaphors with the syntactic structure of a language by studying it from the perspective of language.…”
Section: Basic Concepts Of Adjectival Grammatical Metaphorsmentioning
confidence: 99%